On‐chip mercury‐free deep‐UV light‐emitting sources with ultrahigh germicidal efficiency - Sharma, Vijay Kumar (2021)
In the current COVID-19 scenario, there is an urgent need for developing efficient and mercury-free deep-ultraviolet (deep-UV) light sources for disinfection applications. AlGaN-based light-emitting diodes (LEDs) may be considered as an alternative, but due to their inherent low efficiencies in the deep-UV spectral region, significant developments are required to address efficiency issues. Here, a mercury-free chip-size deep-UV light source is shown which is enabled by high-vacuum chip-scale cavity sealing overcoming the limitations of both mercury lamps and deep-UV LEDs. These deep-UV chips are cathodoluminescence based, in which a cavity is created with high vacuum integrity for efficient field-emission. These chips demonstrate optical output power ≥20 mW (efficiency ≈4%) and, owing to the spectral overlap of phosphor cathodoluminescence spectra and germicidal effectiveness curve, resulted in log 6 (99.9999%) germicidal efficiency. Additionally, these chips offer high reliability, “instant” ON/OFF capability, high operational lifetimes, and low-temperature dependence with complete design freedom.